Nolz1 expression is required in dopaminergic axon guidance and striatal innervation - Clement Soleilhavoup (Nature Portfolio, 2020)
The mechanisms regulating midbrain dopaminergic innervation during development are unclear. Here, the authors showed that Nolz1 is required for axonal guidance of dopaminergic neurons during embryonic development of the mouse brain.